(untitled) (Journal of Medicine, 2018)
Coronary arteries anomalies are an uncommon congenital heart disease. Anomalous origin of three separate ostia is the rarest condition. Hypertrophic cardiomyopathy is the most common inherited disease. There have been just few cases of hypertrophic cardiomyopathy in relation with congenital coronary anomaly. In this report, we describe a rare case of anomalous origin of all three coronary arteries from separate ostia with apical hypertrophic cardiomyopathy. J MEDICINE JUL 2018; 19 (2) : 136-137